GLP-2 regulation of intestinal lipid handling - Mukherjee, Kundanika; Xiao, Changting (Frontiers in Physiology, 2024)
Lipid handling in the intestine is important for maintaining energy homeostasis and overall health. Mishandling of lipids in the intestine contributes to dyslipidemia and atherosclerotic cardiovascular diseases. Despite advances in this field over the past few decades, significant gaps remain. The gut hormone glucagon-like peptide-2 (GLP-2) has been shown to play pleotropic roles in the regulation of lipid handling in the intestine. Of note, GLP-2 exhibits unique actions on postprandial lipid absorption and post-absorptive release of intestinally stored lipids. This review aims to summarize current knowledge in how GLP-2 regulates lipid processing in the intestine. Elucidating the mechanisms of GLP-2 regulation of intestinal lipid handling not only improves our understanding of GLP-2 biology, but also provides insights into how lipids are processed in the intestine, which offers opportunities for developing novel strategies towards prevention and treatment of dyslipidemia and atherosclerotic cardiovascular diseases.